“Sugar” tumor lung. Rare clinical case - A. I. Shevchenko; Yu. O. Shatovskyi; A. P. Melnychuk; O. M. Andrianov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2018)
Aim. Determination of the degree of malignancy and prognosis of the disease in patients with a “sugar” lung tumor.